PERANAN BACAAN SHALAWAT NABI DENGAN METODE MHALUL QIYAM DALAM MENINGKATKAN PSYCHOLOGICAL WELL BEING SANTRI MUBTADI’ DI PONDOK PESANTREN SABILUL HASANAH BANYUASIN - Abdur Razzaq; Syukuria Listiani (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
Pondok Pesantren Sabilul Hasanah is an educational institution that further improves education in terms of Islam. However, the enrichment of the environment and the way of learning is difficult for the santri-santri mubtadi ', thus causing their mind and soul to feel uneasy. This activity is held every Friday night and is very instrumental in Psychological Well Being (peace of soul) santri. Because this activity contains about the glory and majesty of Prophet Muhammad SAW, which if read will give peace to the listener without him have to understand the meaning. The formulation of the problem in this research is: how the role of boarding school Sabilul Hasanah in building Psychological Well Being santri Mubtadi 'through reading shalawat Mahalul Qiyam method? Data analysis techniques used are qualitative data analysis techniques. The method used is Sampling Technique Method, data collection techniques used are Observation, Interview, and Documentation techniques. From the results of the research obtained from the interviews and observations are: that the activity of shalawat in the mawlid Simtudduror is very instrumental to Psychological Well Being (peace of soul) students Mubtadi 'in raising the love of the Prophet Muhammad SAW, understand the beauty of life with the affection of his parents, and also in the process of self-adaptation to the new environment he first undergo.